2013
DOI: 10.3126/njst.v13i2.7722
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Toxic Metal from Aqueous Solution by Using a Biowaste -Used Tea Leaves

Abstract: In the present work an efficient and cost-effective biosorbent was prepared by chemical modification of tealeaves. Amine-functional group was introduced on the surface of adsorbent using dimethylamine. The adsorbent was characterized by SEM, FTIR and elemental analysis. The adsorption capacity of the adsorbent for Cd (II) was determined as the function of pH of the solution, concentration of metal ions and contact time. The maximum adsorption was found to be 77 mg/g at pH 6. Nepal Journal of Science and Techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…However many studies have been made and revealed that maximum adsorption of metal occurred at a low concentration of metal. 30,31 In the present case, it was 25 mg/l while in case of Karnib et al 15 was 30 mg/l. Same results has been observed by Kamble et al 20 adsorption was maximum at PACC (90.5%) > PACB (87.5%) > CAC (85.5%) in a solution containing 25 mg/l concentration of Cu for all PACs.…”
Section: Effect Of Contact Time On Adsorption Of Co (Ii)contrasting
confidence: 43%
See 2 more Smart Citations
“…However many studies have been made and revealed that maximum adsorption of metal occurred at a low concentration of metal. 30,31 In the present case, it was 25 mg/l while in case of Karnib et al 15 was 30 mg/l. Same results has been observed by Kamble et al 20 adsorption was maximum at PACC (90.5%) > PACB (87.5%) > CAC (85.5%) in a solution containing 25 mg/l concentration of Cu for all PACs.…”
Section: Effect Of Contact Time On Adsorption Of Co (Ii)contrasting
confidence: 43%
“…-2B). However, many studies revealed that the increasing contact time has led to increase in adsorption of metal 30,20 but remains stable with a further increase in contact time. 29 Our results had shown the same trend for contact time.…”
Section: Effect Of Contact Time On Adsorption Of Co (Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorbent was then aminated with dimethylamine. The procedures used are similar to those earlier reported [19]. The prepared sample was called Modified tea leaves (MTL).…”
Section: Adsorbent Chemicals Reagents and Instrumentationsmentioning
confidence: 99%